Hydrodynamic Interactions Between Macroalgae and Their Epibionts - Koehl, M.A.R.; Daniel, Thomas L. (Frontiers in Marine Science, 2022)
Macroalgae provide surfaces where other organisms live. Unlike organisms on rigid substrata, epibionts on host macroalgae sit on flexible surfaces that bend, stretch, and move in turbulent water currents and waves. We used blade-like red algae, Mazzaella splendens, and encrusting byrozoans, Membranipora membranacea, to investigate the biomechanical and hydrodynamic effects of encrusting epibionts on macroalgae, and of flexible hosts on epibiotic bryozoans. Passive flapping by algae in wave-driven ambient flow enhanced renewal of water near hosts and epibionts. Wave exposure and the presence of a surrounding canopy of flexible algae altered the locations along algal blades where bryozoans encountered the highest boundary shear velocities. Hydrodynamic forces on flexible algae moving back-and-forth with the water were lower in waves than in unidirectional flow. Bryozoan epibionts increased hydrodynamic forces on host algae by affecting their reconfiguration in moving water. Encrusting bryozoans increased the flexural stiffness of algal blades, but the elastic modulus, extensibility, and strength of blade tissue was unaffected by bryozoan epibionts. Algal blades were more extensible and stronger than bryozoans, so bryozoans fractured or popped off stretched algae. Algae in rapid-flow habitats had few epibionts, and encrusted algae transplanted from a protected to a wave-exposed habitat lost their epibionts.